Kreasi Bentuk Bulu Merak Sebagai Motif Dalam Fashion - Delfita Yeni (SULUH: Jurnal Seni Desain Budaya, 2018)
This study aims to develop creativity in the work of art that is inspired by peacock feathers, the shape of peacock feathers made with embroidered techniques, batik and sequins. The method used in the process of making works through three stages of craft art creation. The first is an exploratory stage that includes exploration activities exploring the source of ideas with the step of identification and problem formulation; searching, extracting, data collection, reference, and data analysis on which to base the design and stage of the work embodiment. Second, the design phase based on the results of data analysis in the form of alternative sketches and sketches selected. The work of shirt and shawl that serves for fashion show and can be used for certain events. The technique used in making the work is by combining the technique of embroidery chain, embroidered stems, embroidered, flat embroidered, embroidered nail leaf, embroidery thorns, and embroidery chains for the embroidery section, while in the whole work combine embroidery on cloth that has been in batik then in sequins.